Effect of common mound building termite (Odontotermes assamensis) on soil properties in tea (Camallia sinensis) gardens of Upper Assam - RAHMAN, I; GOGOI, I; BISWAS, S P (The Indian Journal of Agricultural Sciences, 2011)
The effects of common mound building termite (Odontotermes assamensis Holm.) on the physical and chemical properties of soil in tea (Camellia sinensis L.) gardens of Upper Assam were studied during 2002-2005. There was an increase in soil moisture content, water-holding capacity and soil porosity ranging from 36.63 to 58.23,73.00 to 98.93, 49.60 to 60.06% respectively and decrease in the bulk density ranging from 0.76 to 1.24 g cm3 in the mound soil of 0 . assamelzsis compared with the adjacent soil of the mound where these fractions varied from 29.50 to 42.20, 32.80 to 60.83, 39.97 to 46.33% and 0.93 to 1.42 g cm3 respectively. There was an appreciable increase in the pH, total nitrogen, available phosphorus and available potassium in the mound soils ranging from 0.16 to 0.26%, 20.43, to 45.20 ppm and 0.09 to 0.16% respectively over that of adjacent soils ranged from 0.05 to 0.13%. 14.57 to 31.93 ppm and 0.04 to 0.09% respectively. The increase or decrease of soil properties due to the influence of 0, assnmen.sis was variable pattern in surface (0-15 cm) and in subsurface soil